The effect of neoadjuvant chemoradiation therapy in resectable pancreatic cancer was independent of intratumoral vascularization - Tomomi Yasue; Reiko Ashida; Ryoji Takada; Kenji Ikezawa; Kazuyoshi Ohkawa; Shigenori Nagata; Teruki Teshima; Hirofumi Akita; Hidenori Takahashi; Yuichiro Doki; Hidetoshi Eguchi (BMC Gastroenterology)
Abstract Aim Contrast-enhanced harmonic endoscopic ultrasound (CH-EUS) has promising potential in the diagnosis of pancreatic tumors, assessment of fibrosis, and prediction of chemotherapy efficacy. We hypothesize that radiation therapy might reduce variations in chemotherapeutic efficacy caused by fibrosis-induced blood flow disparities, as we explored the relationship between CH-EUS patterns and the efficacy of neoadjuvant chemoradiotherapy (NACRT) in resectable pancreatic cancer (PC). Methods Patients with resectable PC who underwent CH-EUS followed by NACRT were retrospectively analyzed. The CH-EUS enhancement pattern was evaluated in the vascular and perfusion phases and classified according to vascularity: Group A, hypovascular in both phases; Group B, isovascular and hypovascular in the vascular and perfusion phases, respectively; and Group C, isovascular in both phases. The relationships between the CH-EUS vascular pattern and the histological response according to the Evans classification to NACRT, recurrence-free survival (RFS) and overall survival (OS) were evaluated. Results Of the 48 enrolled patients, 31, 11, and 6 were classified into Groups A, B, and C, respectively. There was no significant difference in histopathological differentiation (p = 0.314) or the efficacy of NACRT (p = 0.282) among the groups. In addition, there was no significant difference between the groups in terms of median RFS or OS, although it was longer than previously reported. Conclusion The histopathological efficacy of NACRT for resectable PC did not differ significantly on the basis of enhancement pattern observed on CH-EUS. NACRT may provide additional therapeutic benefit independent of blood flow considerations.